Brassiere needs of post-mastectomy women (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2005)
Brassieres are foundation garments that support and enhance the female figure. Breast surgery often affects the appearance and form of the women's chest especially for those who had one breast removed and therefore had problems in keeping a balanced shape. Brassieres play a very important role in this regard. The objective of the study was to determine the brassiere needs of selected post-mastectomy women through a survey using a three-part questionnaire. Eighty-one respondents were purposively chosen among breast cancer patients from East Avenue Medical Center and Philippine General Hospital. The study described how the surgical treatments affected the post-mastectomy women's appearance. It was found that the current brassieres of the respondents did not meet their needs. For some of the selected women, their current brassieres made them feel hot, heavy, and were irritating to their bodies when worn. Most of the respondents said they were happy with their brassieres however when asked if they like their brassieres custom-made, 68% agreed and more than 80% would like to buy brassieres from stores specializing in post-mastectomy undergarments. It is recommended that post-mastectomy brassiere designs be proposed and produced at affordable prices for Filipino post-mastectomy women.